APLIKASI THERMOKOPEL TYPE "K" PADA PEMANAS AIR - Muhammad Adam (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
Water heaters (water bath),often used as a tool to heat a meterial or device withadjustable temperature as desired. Water heater said to be good if the ability of the temperature setting can be relied upon.